Camillo e Giulio Cesare Procaccini per i governatori spagnoli a Milano: alcuni episodi di committenza e collezionismo - Odette d'Albo (Boletín del Museo del Prado)
Camillo (1561-1629) and Giulio Cesare Procaccini (1574-1625) were two of the most important painters in Milan at the beginning of the 17th century, when Lombardy was under Spanish control. The article explores the relationships of these artists with three governors —Pedro de Toledo Osorio, V Marquis of Villafranca del Bierzo (1557-1627), Gómez Suárez de Figueroa y Córdoba, Duke of Feria (1587-1634) and Gonzalo Fernández de Córdoba (1585-1635)— sent by the Spanish crown to rule the Milanesado for fifteen years, from 1615 to 1629. These noblemen were refined patrons and collectors of both the Procaccini brothers. Two paintings, Camillo’s Presentation of Jesus at the Temple and Giulio Cesare’s The Agony in the Garden, both commissioned by the Marquis of Villafranca, are now part of the collections of the Museo del Prado.